Coupling cyclic and water retention response of a clayey sand subjected to traffic and environmental cycles. Issue 12 (11th August 2021) - Azizi, Arash; Kumar, Ashutosh; Toll, David G.
Abstract : Compacted soils used as formation layers of railways and roads continuously undergo water content and suction changes due to seasonal variations. Such variations together with the impact of cyclic traffic-induced loads can alter the hydro-mechanical behaviour of the soil, which in turn affects the performance of the superstructure. This study investigates the impact of hydraulic cycles on the coupled water retention and cyclic response of a compacted soil. Suction-monitored cyclic triaxial tests were performed on a compacted clayey sand. The cyclic response of the soil obtained after applying drying and wetting paths was different to that obtained immediately after compaction. The results showed that both suction and degree of saturation are required to interpret the cyclic behaviour. A new approach was developed using (i) a hysteretic water retention model to predict suction variations during cyclic loading and (ii) Bishop's stress together with a bonding parameter to predict accumulated permanent strain and resilient modulus. The proposed formulations were able to predict the water retention behaviour, accumulated permanent strains and resilient modulus well, indicating the potential capability of using the fundamentals of unsaturated soils for predicting the effects of drying and wetting cycles on the coupled soil water retention and cyclic response.